The known unknowns: understanding slow-growing bacteria and their plant interaction through reverse ecology approaches - Gonçalves, Osiel Silva (2023)
The cultivation of bacteria that exhibit slow growth rates has posed a longstanding challenge in microbiology, resulting in a significant number of unculturable bacterial species. This phenomenon, known as the "great plate count anomaly", represents one of the oldest unresolved topics in the field. Recent advancements in cultivation techniques have shown promise in overcoming this challenge. In addition, the study of slow-growing bacteria and their interactions with plants has gained significant attention due to their ecological importance and potential applications in agriculture. Genomics techniques have provided valuable insights into the genetic characteristics underlying microbe-plant interactions. In this context, by examining the in-cultivation techniques, genomics, and computational modeling, we seek to shed light on the slow-growing bacteria and uncover their contributions to ecosystem functioning and plant interaction. Our initial understanding was obtained through the study of 92 slow-growing bacteria isolated from the Brazilian Cerrado soil during a four week-long isolation period. These bacteria can thrive in low-water conditions, promote plant growth, and belong to a novel species group. Genome analysis of five strains revealed their potential in biogeochemical cycles, plant growth promotion, and biosynthesis of secondary metabolites. Next, we conducted greenhouse experiments to assess the efficacy of these bacteria in soybean cultivation, employing a carefully designed bacterial consortium based on our comprehensive understanding of microbial-microbe and plant-microbe interactions. The results showed promising outcomes for improving soybean productivity. In the third chapter of this thesis, we employed in-silico modeling to design a synthetic microbial community aimed at enhancing the yield of important crop plants. By selecting six hub species with essential plant growth-promoting traits from the dominant plant species found in the Campos rupestres, we aimed to optimize the plant-microbe interactions and maximize crop productivity. Lastly, our analysis of 758 metagenome- assembled genomes shed light on the global distribution of the Acidobacteriota phylum and its interactions with plants and biogeochemical processes. This exploration revealed distinct ecological roles for individual taxonomic groups within this phylum, providing valuable insights for future research. Overall, our thesis contributes to a better understanding of slow-growing bacteria, their ecological significance, and their potential applications in agriculture, offering insights into ecosystem functioning and plant interactions. Keywords: Agriculture. Slow-growing bacteria. Ecosystems. Genomics. Microbe-plant interactions. Microbiology